Keaktifan Berkomunikasi dalam Penyuluhan Kesehatan tentang Kematangan Reproduksi Mempengaruhi Promosi Kesehatan pada Remaja SMP BBS Padang Tahun 2022 - Eka Seba Marta (Jurnal Amanah Kesehatan, 2022)
Adolescence is a transitional phase from childhood to adulthood. The characteristic that can be seen is that there are many changes that occur, both physical and psychological changes. The importance of knowing the physical changes of each teenager so that they do not fall into premarital sex with all the consequences. Based on the initial survey conducted from 4 respondents, 6 teenagers did not know about reproductive maturity and 3 teenagers did not know about reproductive maturity. The purpose of the study was to determine the activeness of communicating in health education about reproductive maturity affects health promotion in adolescents. This type of analytic research with cross sectional design. The population in this study was 36 people and the total sample was sampling. The study was conducted on May 02 – August 25, 2022. Data were collected and analyzed univariately and bivariately using Chi Square statistical tests showing that Communicating Activeness in Health Counseling About Reproductive Maturity Affects Health Promotion in Adolescents BBS Middle School in 2022.